A STUDY ON VISUAL QUALITY OF TOURISM ACCOMODATION IN ECO-TOURISM SITE IN PAYA INDAH WETLANDS, MALAYSIA - MOHD KHER BIN HUSSEIN NOORIZAN BTE MOHAMED (ASEAN Journal on Hospitality and Tourism, 2006)
Visual quality is very important as observer's first response to his/her surrounding to the ecotourism site. This factor should be stressed for eco-tourism sites such as wetland. An ecofriendly design of eco-tourism accommodations that harmonize and compatible to natural surrounding could increase the tourist interest to the place itself. A study was conducted in Paya Indah Wetlands aimed at assessing visual quality and perception of the eco-tourism accommodations using expert judgment technique. This study used selected photographs of the accommodation elements in Paya Indah Wetlands representing different types of buildings, park furnitures, parking features, pedestrian facilities, drainage and signages. The scoring scheme for visual quality and landscape features was valued using the six basic design elements, namely, form, line, colour, texture, shape and space. Data were gathered from 100 experts using a structured questionnaire with surrogated photos, distributed equally among landscape architects and architects. The results revealed that the visual quality of Paya Indah Wetlands accommodations were categorized as moderate in quality and some of the elements were considered as of poor quality. From the results, visual quality of the eco-tourism accommodations should be taken into consideration at the early stage in the development process to lend a higher visual quality to the wetland landscape of Paya Indah Wetlands.